2015
DOI: 10.1017/jfm.2015.214
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a low-viscosity near-wall film on bypass transition in boundary layers

Abstract: Bypass transition in a two-fluid boundary layer is examined using direct numerical simulations. A less viscous wall film is considered and the impact on transition location is evaluated at two different viscosity ratios and free-stream turbulence intensities. The less viscous wall film absorbs the mean shear from the outer stream, weakens the lift-up mechanism, and alters the disturbance field inside the boundary layer. These effects all favour a delay in the onset of bypass transition. However, the viscosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We adopt an Eulerian-Eulerian model to simulate the motion and deformation of the incompressible, viscous, hyperelastic layer interacting with an incompressible flow (Sugiyama et al 2011). In order to identify the fluid-solid interface, we employ a conservative level-set approach (Jung & Zaki 2015;You & Zaki 2019). The non-dimensional mass conservation and momentum equations in terms of the velocity field u, pressure p and stress tensor σ are unified over the entire domain…”
Section: Problem Set-up and Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopt an Eulerian-Eulerian model to simulate the motion and deformation of the incompressible, viscous, hyperelastic layer interacting with an incompressible flow (Sugiyama et al 2011). In order to identify the fluid-solid interface, we employ a conservative level-set approach (Jung & Zaki 2015;You & Zaki 2019). The non-dimensional mass conservation and momentum equations in terms of the velocity field u, pressure p and stress tensor σ are unified over the entire domain…”
Section: Problem Set-up and Governing Equationsmentioning
confidence: 99%
“…Our numerical method has been extensively validated for studies of transition and turbulence in Newtonian and viscoelastic flows (Lee & Zaki 2017;Esteghamatian & Zaki 2019, 2021; the latter feature the upper convective derivative seen in the evolution equation (2.6) for B. Validation of the interface tracking algorithm was reported by Jung & Zaki (2015) who computed the evolution of the Zalesak disc (Zalesak 1979) and the evolution of linear and nonlinear instability waves in two-fluid flows (Cheung & Zaki 2010. In Appendix A, we present an additional validation case to show the accuracy of our two-phase solver in predicting the deformation of a neo-Hookean elastic particle in shear.…”
Section: Computational Detailsmentioning
confidence: 99%
“…A level-set function is defined at the inflow plane and tags, or differentiates, the fluid within the boundary layer () and the free stream (). The transport equation of is and therefore is a diffusion-free scalar that serves as a virtual sharp interface between the two fluids; full details of the implementation and exhaustive validation are provided elsewhere (Jung & Zaki 2015; You & Zaki 2019). The value is adopted as the threshold for conditional sampling of the boundary-layer and free-stream fluids.…”
Section: Simulation Set-upmentioning
confidence: 99%
“…The results presented provide an explanation of the mechanism by which a wall film can delay transition in boundary layers beneath free-stream turbulence and complement recent non-linear simulations. 3 A judicious choice of the film viscosity can significantly weaken the amplification of boundary layer streaks, while avoiding any interfacial instabilities. Weaker streak distortions reduce the likelihood of secondary instability 50,51 and hence delay transition to turbulence.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by the formation of high-amplitude boundary-layer streaks and early breakdown to turbulence. 2 Recent direct numerical simulations 3 have demonstrated that introducing a wall film with a carefully selected viscosity can stabilize the outer boundary layer and delay bypass transition. The streaks which precede transition onset were weaker in amplitude than in the single-fluid configuration, and the stabilizing influence of the film was evident despite the potential that the two-fluid interface introduces new instability mechanisms.…”
Section: Introductionmentioning
confidence: 99%